الخیا ا رت الإست ا رتیجیة للخروج من التبعیة للمحروقات وتحقیق التنمیة المستدامة - adem, rahmoune (Finance and Business Economies Review, 2018)
The renty nature of the Algerian economy and its dependence on a single source of income (oil) has made it a staple of this depleted natural resource. The oil potential of the country has become, over time, a curse manifested in the economic crises in Algeria and the resulting imbalances The decline of the industrial and agricultural sectors and other negative symptoms. The aim of this study is to demonstrate the importance of sustainabl اdevelopment and to clarify the energy alternatives that are acquired by the non-renewable energies and non-energy alternatives